Alarming serum antiprotease levels in axial spondyloarthritis - Ayhan Kul,; Zeynep Tüzün,; Muhammet Çelik, (Archives of Rheumatology, 2024)
Objectives: The objective was to assess the serum levels of secretory leukocyte protease inhibitor (SLPI) and elafin in individuals diagnosed with axial spondyloarthritis (AxSpA) and analyze their diagnostic significance and correlation with disease activity. Patients and methods: The case-controlled, cross-sectional study was conducted between August 2021 and April 2023. Sixty patients diagnosed with AxSpA (n=60) were classified according to imaging results as nonradiographic AxSpA (nr-AxSpA [n=30]; 15 males, 15 females; median age: 30 years; range, 27.6 to 34.1 years) and radiographic AxSpA (r-AxSpA [n=30]; 19 males, 11 females; median age: 33 years; range, 30.6 to 38.1 years), forming two patient groups (the nr-axSpA and r-axSpA groups). A total of 30 age- and sex-matched healthy controls (16 females, 14 males; median age: 33 years; range, 29.2 to 37.1 years) were included. Demographic data, laboratory, and clinical characteristics of the participants were recorded. Results: There was no significant difference between SLPI and elafin serum levels in the disease groups. SLPI and elafin levels in AxSpA and nr-AxSpA groups were significantly higher compared to the control group (p<0.05). Based on receiver operating characteristic analysis, the diagnostic values of both parameters were found to be significant in the Ax-SpA and nr-AxSpA groups (p<0.05). There was no significant correlation between serum levels of SLPI and elafin and disease activity parameters. Significant positive correlations were found between SLPI and elafin in both the nr-AxSpA (p<0.05, r=0.870) and r-AxSpA (p<0.05, r=0.725) groups. Conclusion: The levels of SLPI and elafin were found to be significantly elevated in patients with AxSpA, particularly in those with nr-AxSpA, compared to the control group. Therefore, SLPI and elafin can be used as therapeutic biomarkers for the diagnosis of AxSpA and nr-AxSpA. However, no relationship was found with disease activity.